Analisis Psikologi dan Nilai Pendidikan dalam Novel “Dendam Si Yatim Piatu” Karya Sintha Rosse - Widiarti Widiarti (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
The novel Revenge of the Orphans by Sintha Rosse tells the story of the life full of struggles of the main character in achieving his goals. This study aims to describe: (1) the psychological aspects of the main character based on Sigmund Freud's theory; (2) educational values in the novel Revenge of the Orphans; and (4) the relevance of personality aspects and educational values in novels with Indonesian language learning. This research is a qualitative descriptive study. The data in this study are in the form of paragraphs contained in the novel and the data sources for the study as well as reference books related to research. The results of this study are the discovery of (1) personality aspects of the id, ego, and superego of the main character, namely Malik, (2) educational values, namely religious values, moral values, social values, and cultural values, (4) the relevance of personality aspects and education values in novels with Indonesian language learning.  Keywords: Novel, psychology literature, educational value.